Electronic Loyalty Flow: AI Chatbots are Changing Generation Z's Shopping Style: Aliran Loyalitas Elektronik: Chatbot AI yang Mengubah Gaya Belanja Generasi Z - Wenny Pebrianti; Dewi; Ahmadi (JBMP (Jurnal Bisnis, Manajemen dan Perbankan), 2025)
This study investigates the impact of artificial intelligence (AI) chatbots and flow experience on e-loyalty within e-commerce platforms, specifically focusing on Generation Z Shopee users in Pontianak City, with customer satisfaction serving as a mediating variable. Employing a quantitative research design with a causal approach, data were collected through a questionnaire distributed to 200 respondents selected via convenience sampling. The analysis was conducted using Structural Equation Modeling (SEM) with SmartPLS 3.0, revealing a positive and significant relationship between AI chatbots and flow experience on both customer satisfaction and e-loyalty. Furthermore, customer satisfaction was found to mediate the relationship between AI chatbots, flow experience, and e-loyalty. These findings provide valuable insights for developing strategies to enhance consumer loyalty in e-commerce, contributing to a deeper understanding of the factors influencing e-loyalty and offering practical implications for e-commerce platform development.